2012
DOI: 10.1038/ncb2555
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical force regulates integrin turnover in Drosophila in vivo

Abstract: Regulated assembly and disassembly, or turnover, of integrin-mediated cell-extracellular matrix (ECM) adhesions is essential for dynamic cell movements and long-term tissue maintenance. For example, in Drosophila, misregulation of integrin turnover disrupts muscle-tendon attachment at myotendinous junctions (MTJs). We demonstrate that mechanical force, which modulates integrin activity, also regulates integrin and intracellular adhesion complex (IAC) turnover in vivo. Using conditional mutants to alter the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 35 publications
11
92
0
Order By: Relevance
“…To understand how myosin turns over at the wound edge, we developed a mathematical model to extract the rates of myosin assembly (k on ) and disassembly (k off ) in the photobleached regions (Pines et al, 2012). Using the model, we estimated the assembly rate constant at the purse string to be 0.012±0.003 s −1 , significantly lower than the 0.050±0.015 s −1 in epidermal cables (P<0.01, Fig.…”
Section: Results and Discussion Myosin Turnover Is Reduced Around Embmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how myosin turns over at the wound edge, we developed a mathematical model to extract the rates of myosin assembly (k on ) and disassembly (k off ) in the photobleached regions (Pines et al, 2012). Using the model, we estimated the assembly rate constant at the purse string to be 0.012±0.003 s −1 , significantly lower than the 0.050±0.015 s −1 in epidermal cables (P<0.01, Fig.…”
Section: Results and Discussion Myosin Turnover Is Reduced Around Embmentioning
confidence: 99%
“…We modelled FRAP using a two-state model (Pines et al, 2012) to describe the association and dissociation of myosin to and from the purse string, with rate constants k on and k off , respectively:…”
Section: Mathematical Modelling Of Frapmentioning
confidence: 99%
“…Intriguing evidence from Drosophila, using a sensor for integrin activation, has suggested that Mn 2+ might be able to activate integrins in vivo, in larval imaginal discs (Helsten et al, 2008). Moreover, reverse and forward genetic approaches in the fly have identified point mutations in Talin and the β-integrin subunit (known as βPS integrin) that have been proposed to modulate activation (Ellis et al, 2014(Ellis et al, , 2011Jannuzi et al, 2002Jannuzi et al, , 2004Pines et al, 2012Pines et al, , 2011Tanentzapf and Brown, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clathrin-mediated endocytosis is essential for turnover and consequently for maintaining adhesions at the MTJs (Yuan et al, 2010). Experiments using inducible mutations that either increased or decreased the mechanical force applied on MTJs have shown that force is a potent regulator of integrin adhesion complex turnover (Hakonardottir et al, 2015;Pines et al, 2012). Increased force results in decreased endocytosis of integrins and an increase in the rate of assembly of new adhesions, which together combine to stabilize integrin-based adhesions (Hakonardottir et al, 2015;Pines et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation